دراسة بصرية لمحيط دمشق القديمة ( لتحقيق الاستمرارية البصرية وانعكاس الداخل على المحيط ) - صقر, علي سليم (Latakia University Journal -Engineering Sciences Series, 2014)
تُعَدُّ صيانة التراث المعماري والعمراني وحمايته من أهم الخطوات والوسائل التي يتم اللجوء إليها لتكريس القيم الأصيلة في المدينة المعاصرة. والدعوة لحماية المباني الأثرية والتاريخية لا يمكن أن تنفصل عن الدعوة إلى الارتقاء بالبيئة التي تقع فيها هذه المباني, لما لها من انعكاس وتأثير على النسيج التقليدي من حيث التناسق والتجانس مع هذا النسيج الأمر الذي يبرز هذا التراث ويساعد بشكل كبير في حمايته من الاندثار والتشوه الناتج عن التوسع العمراني الحديث واختراقه لهذا النسيج بشكل عشوائي من خلال المسارات الرئيسية العابرة له حتى تصل إلى القلب, بالتالي يكون الاهتمام بهذه المنطقة الانتقالية بين النسيج التقليدي والنسيج الحديث ضرورة حتمية. إن المشاكل التي تعاني منها هذه المناطق هي إحدى المشاكل التي تعاني منها المدينة القديمة حيث يظهر التنافر لدينا بين الصورة البصرية للمبنى التاريخي وصورة المبنى الجديد من حيث اللون والطابع، وهو الأمر الذي ينعكس سلباً على المبنى التاريخي ويفقده قيمته المعمارية, وذلك يؤكد ضرورة تسليط الضوء على هذه المناطق عند دراسة المدن القديمة. وانطلاقاً من ذلك كان من أهم التوصيات لحل مشاكل التراث العمراني الانتباه إلى المناطق الفاصلة بين القديم والحديث وذلك من خلال دراسة تحدد منطقة تحافظ على سيطرة المدينة القديمة, هذه المناطق التي يمكن أن نطلق عليها اسم (المناطق الانتقالية). وللوصول إلى أهداف البحث سيتناول البحث دمشق القديمة ومحيطها والمداخلات المعمارية الحديثة التي أدت إلى هذا التشوه . Both maintenance and preservation of architectural and urban heritage are considered as the most important steps and procedures employed to sustain the original values in the modern city. Due to their effect and impact upon the traditional tissue in terms of their harmony and homogeneity with this tissue, the call to preserve archaeological and historical buildings is inseparable from the call to upgrade the environment where such buildings are located. Thus, this showcases such heritage and extremely helps in protecting it from either extinction or the deformity caused by modern urban sprawl and its random penetration of this tissue through the main routes across it up to its very core. Hence, the concern with this transitional area between the traditional tissue and the modern tissue becomes an inevitable necessity. The problems that these areas suffer from are one of the problems facing the old city where discord lies between the v image of the historical building and the image of the new building in terms of both color and style. As a result, this negatively affects the historical building as it makes it lose its architectural value. This emphasizes the necessity to shed light on such areas while studying old cities. Accordingly, one of the most important recommendations in order to solve the problems of the urban heritage is to pay attention to the areas separating between the old and the new. This can be achieved through a study that defines an area that maintains the dominance of the old city. Such areas can be called the (transitional areas). In order to achieve the aforementioned aims of the research, the research will deal with old Damascus city and its surrounding, in addition to modern architectural interventions which had led to such deformity.